Investigating social network patterns within an empathic online community for older people - Pfeil, Ulrike; Zaphiris, Panayiotis (My University, 2009)
In this paper, we study the social network structure of an online discussion board within SeniorNet, an empathic online community for older people. We apply Social Network Analysis (SNA) to analyse the communication patterns and relationships between members of the discussion board. In addition to looking at the structure of the exchanged messages within the discussion board as a whole, we also investigate associations between the communication content and the social network patterns. Our findings show distinct differences between the social network patterns of empathic and non-empathic communications. For example, members are more connected and closer to each other in the social networks that are based on empathic communication compared to non-empathic communication. Additionally our results show that the type of empathic communication (e.g. different kinds of support) is linked to the social network structure within the discussion board.
Keywords: Empathic online communities; Older people; Social network analysis; Social interactions; Ageing; Online discussion board; CMC